2021
DOI: 10.1186/s12936-021-03971-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic diversity of Plasmodium falciparum circumsporozoite protein in Sudan: the RTS,S leading malaria vaccine candidate

Abstract: Background The currently used malaria vaccine, RTS,S, is designed based on the Plasmodium falciparum circumsporozoite protein (PfCSP). The pfcsp gene, besides having different polymorphic patterns, can vary between P. falciparum isolates due to geographical origin and host immune response. Such aspects are essential when considering the deployment of the RTS,S vaccine in a certain region. Therefore, this study assessed the genetic diversity of P. falciparum in Sudan based on the pfcsp gene by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…This result was attributed to the sample sizes [ 31 ]. Larger sample size from other different regions and the selected regions of this study might provide different results if this insertion occurs by chance in the Sudanese Pfcsp gene [ 32 ]. The N-terminal region can be an attractive component of PfCSP-based vaccine due to the N-terminus of imported Pfcsp was relatively conserved.…”
Section: Discussionmentioning
confidence: 99%
“…This result was attributed to the sample sizes [ 31 ]. Larger sample size from other different regions and the selected regions of this study might provide different results if this insertion occurs by chance in the Sudanese Pfcsp gene [ 32 ]. The N-terminal region can be an attractive component of PfCSP-based vaccine due to the N-terminus of imported Pfcsp was relatively conserved.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of the genetic variants that circulate in a region is essential in order to establish the potential efficiency of prophylactic vaccines. This was demonstrated in the currently used malaria vaccine against Plasmodium falciparum in Sudan and other African countries [ 51 ]. On the other hand, previous studies related to the evaluation of the genetic diversity of other neglected tropical parasites have provided relevant information about the strategies related to the mitigation of transmission or the effectiveness of the control, as in the case of Plasmodium vivax in the southeast of Mexico [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The chances of Anopheles to encounter the parasite in the blood meal of infected human can be very high during the peak transmission season [ 30 , 38 , 47 ]. This can affect significantly the role of vector population in transmitting malaria, such as described by Guelbéogo et al [ 47 ], who reported a high frequency of Anopheles coluzzii engorged females with human-animal mixed blood meals.…”
Section: Discussionmentioning
confidence: 99%
“…Using the semi-nested PCR, the primers used for the detection of the 4 human malaria parasites in Sudan including P. falciparum, P. vivax, Plasmodium ovale , and Plasmodium malariae were adopted from Rubio et al [ 37 ] including; UN-R: 5′ GAC GGT ATC TGA TCG TCT T 3′, UN-F: 5′ AGT GTG TAT CAA TCG AGT TT 3′, for the first PCR reaction and UN-F primer and Fal-R: 5′ AGT TCC CCT AGA ATA GTT ACA 3′, Viv-R: 5′ AGG ACT TCC AAG CCG AAG 3′, Ova-R: 5′ GCA TAA GGA ATG CAA AGA ACA G 3′, and Mal-R: 5′ GCC CTC CAA TTG CCT TCT 3′, for the second PCR reaction to confirm the presence of Plasmodium species. PCR cycling condition was adjusted according to Mohamed et al [ 38 ]. Positive DNA of P. falciparum, P. vivax, P. ovale , and P. malariae were used as positive controls in each PCR run.…”
Section: Methodsmentioning
confidence: 99%